The first report of living donor liver transplantation for abernethy malformation (congenital absence of the portal vein) in Vietnam - Thanh Le Van; Dung Dao Duc; Nam Hoang Duc; Quang Vu Van (Elsevier, 2020)
Abernethy malformation, also known as Congenital absence of the portal vein (CAPV), is a very rare malformation. There are some reports of liver transplantation as a treatment for CAPV, and our report is the first case in Vietnam. A 10-year-old boy, diagnosed with Abernethy type 1b malformation (portal vein draining directly into the inferior vena cava) and liver tumor. Living donor liver transplantation was performed using a right liver graft from his mother. Histopathological examination of the native liver showed a huge mass lesions within the right liver and absence of portal vein in portal space. Postoperatively, the patient attained optimal liver function and at a 13-month follow-up has returned to normal life. Keywords: Congenital absence of the portal vein, Abernethy malformation, Liver transplantation